On the binding of iota-carrageenan towards Pb2+, Cd2+, and Zn2+ : its mechanism and the effects of molecular weight and the presence of K+, Na+, and Ca2+ - Apodaca, Dahlia C. (Animo Repository, 2001)
Previous studies have indicated that the iota- and the kappa- types of carrageenans are capable of binding with Pb, Cd and Zn ions and that the iota-carrageenan exhibits a higher metal binding capacity. The good metal sorbing property of iota-carrageenan suggests its possible participation in the removal of heavy metals in water, wastewater, soil samples and others. However, the potential application of iota-carrageenan for environmental remediation depends on the understanding of the mechanism involved.This study deduces the mechanism involved on the binding of iota-carrageenan towards Pb, Cd and Zn metal ions. Electrostatic attraction and ion exchange predominate, consistent with the BM0.5 or B2M complex model. K and Na ions are significantly displaced by Pb, Cd and Zn ions. Results also show preferential binding of Ca2+ by iota-carrageenan. Comparison of the exchange capacity status, sulfate content and the metal binding capacity of iota-carrageenan indicates that other binding mechanisms also exist in high molecular weight iota-carrageenan.The binding capacity of iota-carrageenan has also been observed to decrease with a decrease on its molecular weight.The iota-carrageenan was found to preferentially sorb Fe3+, Ni3+, Al3+, Si4+, and Ca2+ in naturally contaminated soil samples. Pb, Cd and Zn ions, present in trace amounts, were not bound.